The Implementation of the Dilemma-STEAM Model in Fluid Dynamics Subjects through the Archimedes Screw Project - Nasbey, Hadi; Sabrina, Putri Marsha; Sari, Ni Larasati Kartika; Muliyati, Dewi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
Physics is one of the sciences that is closely related to daily life, one example being fluid material material. However, the understanding of physics, especially fluid material, is still relatively low. These problems can be overcome by applying a learning model that is integrated with teaching materials that have developed over time. The dilemma STEAM learning model is a learning model that can help students to understand physics based on students' experiences. The dilemma STEAM learning model has five learning stages that can make learners recognize the problem, find solutions, and then solve the problem. This study aims to develop teaching materials based on the dynamic dilemma STEAM learning model based on the dilemma STEAM learning model. The development of the Archimedes Screw Project equipped with E-Modules as teaching materials was developed using the ADDIE development model. The ADDIE development model has several stages, namely Analysis, Design, Development, Implementation, and Evaluation. E-Modules are made using the Canva application which can be accessed anywhere and anytime. After the E-Module was developed, the next stage was the feasibility test of the E-Module by experts. The results of the feasibility test by media experts obtained a result of 88.3% with a very feasible category. Meanwhile, the results of the feasibility test by material experts obtained a result of 84% with a very feasible category. And the results of the feasibility test by learning experts obtained a result of 83.3%. And the readability of the E-Modul by the student after using it is 72.4% with a good read, which is demonstrated by the success of the student assembling Archimedes Screw by following five stages of the dilemma STEAM learning model.